THE EFFECT OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION ON QUALITY CULTURE AT PT LONDON SUMATRA - Amalia Trihapsari; Juniarti; Ameliya Adisty; Anita Br Sinambela; Fara Dhia Naaura (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
This study aims to determine the influence between total quality management on the quality culture of case studies at PT London Sumatera-Medan. The research approach carried out in this study is associative / quantitative. The population of this study is managers and employees of PT London Sumatera-Medan totaling 40 people. The sampling method used is census i.e., making the entire population a sample in this study. So that the number of samples is 40 respondents. The analysis method used in writing this thesis is an analysis technique with a simple linear regression method with SPSS software application tools. The results showed that Total Quality Management has a positive and significant effect on Quality Culture.